Ross Errilly Franciscan Friary, north chancel wall, tomb niche, jamb, arch and hood moulding - O'Donovan, Danielle (My University, 2008)
Moulding of tomb niche, jamb and arch moulding from intrados comprises: hollow chamfer, right-angled rebate, hollow chamfer, quadrant. Hood comprises frontal fillet, hollow chamfer. In design, the tomb niche looks like those from Quin and Ennis, which are related to the Limerick/Kerry examples. The moulding looks very like that of the west door.
Tomb niche
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Funerary Monuments; Architecture, Franciscan; Late Medieval; roll moldings; moldings, hollow; hood moldings